EFL Teachers’ Culture, Teaching Perspectives and Practices - Zaid, Hassan (International Journal of Language and Literary Studies, 2025)
This study explores Moroccan English as a Foreign Language (EFL) teachers’ perceptions and practices related to teaching culture. A quantitative survey design was used to gather data from 60 EFL teachers. Descriptive statistics were used to explore teachers’ culture teaching perceptions and instructional practices in classes. First, the results reveal that most teachers acknowledge the importance of incorporating culture into language teaching, perceiving it as both a fundamental aspect of language teaching and crucial for reinforcing students’ cultural identities. Teachers also expressed favorable views towards intercultural education, considering it important to foster tolerance. However, opinions vary on whether students need advanced language proficiency before engaging in cultural learning. Second, Teachers use a variety of cultural activities, including dialogues, role-plays, cultural comparisons, and authentic materials to teach culture in their classrooms. However, certain activities, such as cultural research projects, and personal cultural narratives are less frequently used. Finally, the pedagogical implications highlight the need for a principled approach that bridges the gap between being aware of the prominence of cultural integration and effectively implementing it in EFL classrooms to cultivate critical intercultural communicative competence to avoid idealization of the target culture and preserve local cultures.